(untitled) (Praxis Educativa, 2012)
An account of the history of education and of the birth and development of schooling up to the most recent educational reforms gives evidence of the difficulty of fostering profound changes. Today´s educational systems have become an instrument in the hands of governments that may go so far as to affect the very structure of the system. Thus, educational policies may create certain conditions to transform school practices. But -as educational research has repeatedly shown- due to a deeply rooted educational culture, they have the power neither to transform nor even significantly improve teacher’s performance. The main problem in educational change lies not so much in its planning as it does in its capacity to put prevailing beliefs about education to question, so as to enable the establishment of more appropriate teaching practices for the educational needs of present-day students. In such process, the role of teachers is essential.